Pengurapan dalam Kitab-Kitab Sejarah Perjanjian Lama - Wassar, Sarah; Jaminter Ompusuggu; Joshua Christian Wenas; Tri Subekti; Yeyen Darmadi (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2021)
When Jesus appeared to the disciples, he said: "Peace be with you..., He breathed on them and said: Receive the Holy Spirit", John. 20:21-22. Not long after that Jesus ascended to heaven. The disciples prayed for ten days in Jerusalem and the Holy Spirit came down as promised by Jesus (Acts 1:8). Apart from that, no one else, whether a prophet, apostle, church father or pastor, can give breath and tell people to receive the Holy Spirit. This research aims to discover Christian views and attitudes in ordaining office or worship services. In this research, the method used is descriptive qualitative with an approach to understanding and comprehending the importance of receiving the anointing from the Holy Spirit so as not to be extreme in completing office or worship services. The Holy Spirit anoints a person so that the person experiences a change in life to become spiritually qualified and has the divine ability to carry out service according to his or her calling, with abilities that surpass human strength.